Analisis Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja di RSUD dr. Djasamen Saragih Tahun 2022 - Corry Tiurma Sitorus (Jurnal Kajian Kesehatan Masyarakat, 2022)
Hospitals are workplaces with various potential hazards that can pose a risk to safety and health of hospital human resources (HR), patients, patient companions, visitors, and the hospital environment. For this reason, a system is needed to minimize the emergence of these potential hazards, namely the application of the Occupational Safety and Health System. This study aims to analyze the application of the Occupational Health and Safety Management System (SMK3) in RSUD dr. Djasamen Saragih, Pematangsiantar City. The type of research is Mix Method. The research location is in RSUD dr. Djasamen Saragih. There were 5 informants in this study. Data collection was done by interview, checklist form according to PP No. 50 of 2012, document review and field observations. The results of the study obtained that the level of achievement of the implementation of SMK3 with the results of the audit in the initial level category, which was 51.56%, was included in the category of Poor implementation. The number of criteria is 64 criteria, where the number of suitable criteria is 33criteria and those that are not suitable are 31 criteria. Commitments in the form of policies have not been made in writing, but commitments in the form of budget funds, supporting facilities and infrastructure such as PPE, K3 signs, evacuation routes in the event of a disaster are already available. The implementation of the K3 plan has not been fully implemented by the K3RS Committee but the hospital's efforts in implementing K3 are also carried out by other units related to K3 such as the PMKP Committee, PPI Committee, IPSRS and Environmental Sanitation Installations. Implementation of the Occupational Health and Safety Management System starting from the Policy Determination stage to performance evaluation at RSUD dr. Djasamen Saragih has not been fully implemented in accordance with the standards stipulated in the Regulation of the Minister of Health No.66 of 2016 and Government Regulation No. 50 of 2012.